Primary Pulmonary Myxoid Sarcoma: A Rare and Challenging Diagnosis in Thoracic Oncology - Apriyanto, Yudi; Febriani, Anna; Wulandari, Laksmi; Wati, Farah Fatma (Jurnal Respirasi, 2025)
Introduction: Primary pulmonary myxoid sarcoma (PPMS) is a rare malignant mesenchymal lung tumor, with fewer than 40 cases reported worldwide. This care report presented a case of PPMS with surgical difficulties. Case: A 53-year-old man presented with a six-month history of exertional dyspnea, coughing up blood, right chest pain, anorexia, and weight loss. Thoracic computed tomography (CT) imaging revealed an enhancing solid mass in the middle-posterior mediastinum. Histopathological examination of a core biopsy identified anaplastic lipoblast cells indicative of liposarcoma. Based on the multidisciplinary team (MDT) discussion, the patient was diagnosed with mediastinal liposarcoma, and tumor excision was planned. However, during the surgery, a lung tumor with adhesions to the middle and lower lobes of the right lung was discovered, precluding the complete tumor. An open biopsy was performed instead, revealing a proliferation of anaplastic cells with round to oval spindle nuclei arranged reticularly within a myxoid stroma, along with positive Alcian blue staining. Immunohistochemical analysis demonstrated focal desmin positivity in the cytoplasm of the tumor cells. The diagnosis of PPMS was confirmed based on the criteria by the World Health Organization (WHO) in 2021, including primary lung tumor, spindle-shaped and round tumor cells in a reticular pattern within a myxoid stroma, and immunohistochemical findings that exclude other histologically similar tumors. Conclusion: Although rare, PPMS should be considered in the differential diagnosis of thoracic tumors. Most PPMS patients were treated surgically and had a good prognosis. However, tumor excision could not be performed in this patient due to the adhesion of the tumor mass to the middle and lower lobes of the right lung.